The family allowance system and unemployment protection: Analysis based on the social intervention model - Lozano Parra, Johan Sebastián; Caballero Palomino, Sergio Andrés; Morantes Franco, Carlos Fernando; Jaimes Melgarejo, María Fernanda (DIXI, 2024)
The object of this research article is to study the family subsidy system in the Colombian State, which is seen as a protectionist model against unemployment. The following question was posed as a problem: does the Family Allowance System allow for a social intervention model that protects the worker against unemployment? The normative framework of the Family Allowance System as a social intervention model for unemployment is analyzed. The methodology used is a basic legal-theoretical one of a correlational, descriptive, explanatory and analytical type. The results obtained made it possible to identify the elements that characterize the system from the normative and jurisprudential point of view. With respect to Law 789 of 2002, the functions assigned to unemployment were established. Finally, the social intervention model was identified and how the family subsidy system is, in itself, a tool that enhances the constitutional principles and the state apparatus for the benefit of workers.